2003
DOI: 10.2176/nmc.43.61
|View full text |Cite
|
Sign up to set email alerts
|

Disconnecting Surgical Treatment of Hypothalamic Hamartoma in Children and Adults With Refractory Epilepsy and Proposal of a New Classification.

Abstract: Hypothalamic hamartoma associated with intractable epilepsy is a major problem when surgical management is discussed. Professor Olivier Delalande is Chief Neurosurgeon of the Department of Pediatric Neurosurgery, Fondation Ophtalmologique Adolf de Rothschild, in Paris, France. In recent international symposia, he has reported a series of hypothalamic hamartoma in children and adults with refractory epilepsy, managed with various surgical techniques according to his new classification of hypothalamic hamartomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
176
0
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 255 publications
(187 citation statements)
references
References 23 publications
2
176
0
9
Order By: Relevance
“…25,26,40,50,52 The feasibility of the disconnection depends on the plane of insertion. The Delalande classification consists of 4 lesion types: Type 1 has a horizontal implantation plane and may be lateralized on one side; Type 2 has a vertical insertion plane and intraventricular location; Type 3 is a combination of Types 1 and 2; and Type 4 includes all giant hamartomas 19 (Fig. 5).…”
Section: Hamartoma Disconnectionmentioning
confidence: 99%
“…25,26,40,50,52 The feasibility of the disconnection depends on the plane of insertion. The Delalande classification consists of 4 lesion types: Type 1 has a horizontal implantation plane and may be lateralized on one side; Type 2 has a vertical insertion plane and intraventricular location; Type 3 is a combination of Types 1 and 2; and Type 4 includes all giant hamartomas 19 (Fig. 5).…”
Section: Hamartoma Disconnectionmentioning
confidence: 99%
“…The hypothesis of an intrinsic epileptogenesis of HH gained impetus after the stereo-EEG demonstration of ictal onsets originating from the hypothalamic lesion, 32 and was further corroborated by subsequent reports showing production of typical gelastic seizures by depth electrode stimulation, ictal SPECT studies demonstrating HH hyperperfusion, and interictal spike source analysis. 4,9,11,12,16,21,22,26,35,45 The epileptogenic activity of HHs has been recently demonstrated at the cellular level: detailed electrophysiological analysis of slices taken from surgical specimens showed the predominance of small GABAergic inhibitory neurons exhibiting an intrinsic "pacemaker-like" behavior. 54 The concept that surgical intervention should mainly target the HH was not easy to accept.…”
Section: Pathophysiology: Intrinsic Epileptogenesis Of Hhsmentioning
confidence: 99%
“…13,15,35 This also reflects the hesitancy of neurosurgeons to operate on a diencephalic lesion stemming from the hypothalamus, which requires a complex procedure followed by a difficult postoperative period in which multiple vascular and metabolic complications (such as diabetes insipidus, SIADH [syndrome of inappropriate antidiuretic hormone], hyperthermia, hyperphagia, and hypothyroidism) may arise. 9,13,24,35,37,44,45 Substantial seizure improvement following resection, disconnection, or ablation is further proof of the intrinsic epileptogenesis of HHs and the need for a direct approach to produce seizure relief. [2][3][4]8,9,[12][13][14][16][17][18]24,25,28,35,36,[44][45][46][47][48]51,52 The degree of seizure control is linked to the extent of the surgical intervention.…”
Section: Pathophysiology: Intrinsic Epileptogenesis Of Hhsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,13 The idea that these lesions can be managed using the quicker and somewhat safer option of endoscopic removal was suggested to me by Dr. Jung Uhn Choi at a neuroendoscopy meeting in Naples in 2003. Although I do not use this approach exclusively, I have found that most HHs within the third ventricle are excellent candidates for this type of excision.…”
Section: Introductionmentioning
confidence: 99%